Rolling contact fatigue internal crack propagation test method based on additive manufacturing
Rolling contact fatigue samples containing internal buried defects were prepared through additive manufacturing, and industrial CT and electric spark cutting technology were used to solve the problem of difficult monitoring of internal crack propagation of rolling contact fatigue, real simulation and research of rolling contact fatigue type II-III composite cracks, and technical support was provided for engineering problems such as railway wheel rim cracks.
Patent Information
- Application Number
- CN202411904389.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to effectively study the expansion mechanism of internal cracks in rolling contact fatigue, especially the inability to truly simulate the expansion of internal cracks and monitor their expansion rate in real time.
Additive manufacturing technology is used to prepare rolling contact fatigue samples containing internal buried defects, and experiments are carried out through rolling contact fatigue testing machines. Industrial CT scanning is used to monitor the expansion of internal cracks, and the morphology and size of cracks are analyzed in combination with electric spark cutting and scanning electron microscopy technology.
Real simulation and real-time monitoring of internal cracks of rolling contact fatigue are realized, the crack expansion rate and expansion path are obtained, and the expansion behavior of rolling contact fatigue II-III composite cracks is effectively reproduced, providing technical support for engineering problems such as railway wheel rim cracks.
Smart Images

Figure CN119804186A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of research on near-surface fatigue crack propagation of rolling components, and in particular to a rolling contact fatigue internal crack propagation test method based on additive manufacturing. Background Art
[0002] Rolling contact fatigue (RCF) refers to the process in which a material produces local permanent cumulative damage under the action of cyclic rolling contact stress, and after a certain number of cycles, pitting or shallow or deep peeling occurs on the contact surface. Wheel rim cracks, rail core damage, and bearing raceway peeling are typical RCF behaviors. Taking railway wheel rim cracks as an example, rim cracks refer to the initiation of fatigue cracks caused by internal inclusions 10-25mm below the wheel tread. As the cracks further expand, they can cause the entire wheel material to fall off, which restricts the service reliability of railway wheels. RCF internal cracks are buried near the surface of the rolling element and are type II-III composite cracks, which are not easy to monitor in real time. There are currently two general methods for studying the propagation of RCF internal cracks: one is to simulate the stress state of the crack for equivalent testing; the other is to use finite element software to simulate the force of RCF internal cracks. There are few studies on the influence of the upper and lower deflections of RCF serrated cracks, the friction of the crack surface, and the magnitude of compressive stress on the propagation of RCF internal cracks.
[0003] At present, there are great difficulties in studying the internal crack propagation mechanism of RCF. First, it is currently impossible to generate real internal cracks in the three-dimensional volume of a raw material without damaging the surface material, and it is very difficult to simulate the operating load of the corresponding components through full-scale bench tests, and the experimental funds are expensive. Secondly, the internal crack size can only be roughly measured by means such as ultrasonic testing, and the crack propagation rate cannot be accurately measured in real time. In order to solve the shortcomings of the existing technology, it is particularly important to provide a rolling contact fatigue internal crack propagation test method based on additive manufacturing.
[0004] Existing research on internal crack propagation in rolling contact fatigue is mostly stress equivalence experimental research. For example, the Chinese invention patent application with publication number CN117330411A discloses an equivalent reduction test method for the crack propagation retardation mechanism of railway wheel rims. The compressive stress and shear stress of the equivalent rim crack are used by a round rod specimen with an annular notch in the middle, and the influence of axial load on crack propagation is studied. The rim crack propagation retardation behavior is reproduced, but the crack propagation caused by rolling contact load is not truly simulated, and the crack is an open crack rather than an internal buried crack. Summary of the invention
[0005] The object of the present invention is to provide a rolling contact fatigue internal crack propagation test method based on additive manufacturing to solve at least one technical problem existing in the above-mentioned background technology.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a rolling contact fatigue internal crack propagation test method based on additive manufacturing, comprising the following steps:
[0008] Prepare rolling contact fatigue main specimens with internal buried defects and defect-free companion specimens;
[0009] Conduct rolling contact fatigue test: pre-treat the specimen to determine the initial defects of internal defects; determine the experimental parameters, start the rolling contact fatigue test machine to run the oil lubrication test under the specified number of cycles;
[0010] The main sample is removed, the contact surface morphology of the sample is photographed, the mass and diameter of the sample are measured, the internal crack extension is photographed using industrial CT, and the process is repeated after the specified number of cycles.
[0011] Obtain the relationship between the major axis and minor axis extension size, extension angle, crack area, equivalent crack size and the number of sample cycles of the elliptical crack inside the main sample under the specified number of times;
[0012] Calculate the growth rate of internal buried cracks;
[0013] After the experiment, the crack area that has not extended to the surface was sampled using an electric spark cutting device and the crack surface was cut open. The crack extension fracture morphology was observed using a scanning electron microscope and a white light interferometer to obtain information such as the size and morphology of the crack.
[0014] Analyze the growth rate and growth behavior of different combined load parameters and different initial cracks.
[0015] Furthermore, the main specimen was manufactured by additive manufacturing technology, and a buried elliptical defect was preset inside each specimen. Finally, the main specimen was processed into an annular specimen with a diameter of 60 mm, a thickness of 20 mm, a rolling boss length of 10 mm, a height of 4 mm, and a radius of 80 mm; the accompanying specimen was processed into an annular specimen with a diameter of 60 mm and a thickness of 20 mm using a rod with the same material and equivalent hardness as the main specimen.
[0016] Furthermore, before the experiment, each main sample was scanned and analyzed using industrial CT to obtain the initial size and position information of the internal defects, the initial diameter of the sample was measured using a vernier caliper, the initial mass of the sample was measured using an electronic balance, the main sample was installed on the driving shaft, and the companion sample was installed on the driven shaft.
[0017] Furthermore, the theoretical contact stress is set to 1500 MPa, and the corresponding experimental vertical load F=1565 N is calculated by the formula. At this time, the stress field at a position 2 mm below the contact surface of the main specimen is similar to the stress field at the rim crack 15 mm below the tread of the actual wheel.
[0018] Furthermore, the rotation speed of the main specimen was set to 1000 rpm, the slip ratio was set to 1%, the lubricating oil was continuously sprayed onto the rolling contact surface of the specimen during the experiment, a filter was additionally provided in the circulation system to regularly dispose of waste chips in the testing machine, and the rolling contact fatigue testing machine was started to run the oil lubrication experiment at a specified number of cycles.
[0019] Furthermore, after running the specified number of cycles, the main sample is removed, ultrasonically cleaned and dried using anhydrous ethanol, the diameter size in the circumferential direction is measured three times with a vernier caliper and the average value is taken, the mass is measured three times with an electronic balance and the average value is taken, the contact surface morphology of the sample is photographed, and the internal crack propagation information of the main sample is recorded using an industrial CT scan, and the specified number of cycles is continued to be run, and the process is repeated until the final set number of cycles is reached.
[0020] Furthermore, the obtained industrial CT scanning data was used to measure the major axis extension size a of the elliptical crack inside the main sample at the specified times. i (i is the specified number of cycles), the minor axis expansion dimension b i , crack extension angle θ i , crack area S i , equivalent crack size Draw a curve diagram of the relationship between the parameters and the number of sample cycles.
[0021] Furthermore, the obtained crack extension size information was statistically analyzed, and the secant method was used to calculate the crack extension rate during data processing:
[0022]
[0023] Where C is the crack extension size, N is the number of cyclic loading;
[0024] The relationship curve between crack extension size and crack extension rate is obtained.
[0025] Furthermore, after the experiment, if the internal crack of the main sample has expanded to the point of surface shedding, the fracture surface will be protected. For the crack area that has not expanded to the point of surface shedding, the electric spark cutting equipment will be used to take samples and cut the crack surface. The scanning electron microscope and white light interferometer will be used to observe the crack extension fracture morphology, and the two-dimensional and three-dimensional information of crack extension will be obtained. By statistically analyzing the width and height of the fatigue crack, the friction and extrusion conditions in the crack area and the grain refinement phenomenon, the crack formation mechanism will be studied, and a comparative analysis will be conducted with the actual internal serrated cracks of rolling contact fatigue to verify the effectiveness of the experiment.
[0026] Furthermore, by changing the experimental vertical force, rotation speed, slip ratio, lubrication conditions, and number of cycles, the effects of different combined load parameters on crack propagation are analyzed, the initial shape, size, and position of the internal buried defects from the contact surface are changed, and the influence of different initial defects on the crack propagation rate and propagation behavior is analyzed.
[0027] The beneficial effects of the present invention are as follows: a metal material sample containing an internal buried defect is prepared by an additive manufacturing method, a rolling contact fatigue experiment is carried out, the expansion of the internal crack is tracked by industrial CT scanning, the expansion size and expansion path of the crack are intuitively measured, and the expansion law of the rolling contact fatigue type II-III composite crack is truly simulated, providing technical support for the research on railway wheel rim cracks, rail core damage, bearing raceway surface peeling and rolling contact fatigue theory.
[0028] Additional advantages of the present invention will be more clearly given in the following description or learned through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0030] Figure 1 This is a schematic diagram of internal crack propagation in rolling contact fatigue according to an embodiment of the present invention.
[0031] Figure 2 This is a schematic diagram of the dimensions of the main sample and the accompanying sample described in an embodiment of the present invention.
[0032] Figure 3 Schematic diagram of the internal stress distribution of the wheel-rail according to an embodiment of the present invention.
[0033] Figure 4 Schematic diagram of internal stress distribution of a sample according to an embodiment of the present invention.
[0034] Figure 5 A CT schematic diagram of a main sample with preset internal defects according to an embodiment of the present invention.
[0035] Figure 6 Schematic diagram of a rolling contact fatigue test device according to an embodiment of the present invention.
[0036] Figure 7 This is a schematic diagram of a scanning electron microscope showing the propagation of a zigzag crack on a wheel rim according to an embodiment of the present invention.
[0037] Figure 8 This is a schematic diagram of white light interference of the rim sawtooth crack extension according to an embodiment of the present invention. DETAILED DESCRIPTION
[0038] The embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below by the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention.
[0039] It should be understood by those skilled in the art that unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs.
[0040] It should also be understood that terms, such as those defined in commonly used dictionaries, should be understood to have a meaning consistent with that in the context of the prior art and will not be interpreted in an idealized or overly formal sense unless as defined herein.
[0041] Those skilled in the art will appreciate that, unless otherwise stated, the singular forms "a", "an", "said" and "the" used herein may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present invention refers to the presence of the features, integers, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements and / or groups thereof.
[0042] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. Different embodiments or examples described in this specification and features of different embodiments or examples may be combined and combined by those skilled in the art without contradiction.
[0043] To facilitate understanding of the present invention, the present invention is further explained below with reference to specific embodiments in conjunction with the accompanying drawings, and the specific embodiments do not constitute a limitation on the embodiments of the present invention.
[0044] Those skilled in the art should understand that the drawings are merely schematic diagrams of embodiments, and the components in the drawings are not necessarily necessary for implementing the present invention.
[0045] Example 1
[0046] In this embodiment, a rolling contact fatigue internal crack propagation test method based on additive manufacturing is provided. A rolling contact fatigue specimen containing internal buried defects is prepared by additive manufacturing. A rolling contact fatigue testing machine is used to change different load parameters for testing. The propagation of internal cracks is observed by industrial CT, mainly to reproduce the internal serrated crack propagation behavior of rolling contact fatigue.
[0047] The rolling contact fatigue internal crack growth test method based on additive manufacturing includes the following steps:
[0048] Step 1: Prepare a rolling contact fatigue main specimen containing internal buried defects and a defect-free companion specimen;
[0049] Step 2: Conduct rolling contact fatigue test;
[0050] 2-1 Pre-treat the sample and determine the initial defects of internal defects;
[0051] 2-2 Determine the experimental parameters and start the rolling contact fatigue testing machine to run the oil lubrication experiment under the specified number of cycles;
[0052] Step 3: Remove the main sample, photograph the contact surface morphology of the sample, measure the mass and diameter of the sample at this time, use industrial CT to photograph the internal crack extension, continue to run the specified number of cycles, and repeat the process;
[0053] Step 4: Obtain the relationship between the major axis and minor axis extension size, extension angle, crack area, equivalent crack size and the number of sample cycles of the elliptical crack inside the main sample at the specified number of times;
[0054] Step 5: Calculate the growth rate of the internal buried crack;
[0055] Step 6: After the experiment, the crack area that has not extended to the surface is sampled using an electric spark cutting device and the crack surface is cut open. The crack extension fracture morphology is observed using a scanning electron microscope and a white light interferometer to obtain the crack size information;
[0056] Step 7: Analyze the growth rate and growth behavior of different combined load parameters and different initial cracks.
[0057] Specifically, in step 1, the main sample is manufactured by additive manufacturing technology (SLM), and a buried elliptical defect is preset inside each sample. Finally, the main sample is processed into an annular sample with a diameter of 60 mm, a thickness of 20 mm, a rolling boss length of 10 mm, a height of 4 mm, and a radius of 80 mm. The size and position of the internal defects are shown in Table 1; the accompanying sample is processed into an annular sample with a diameter of 60 mm and a thickness of 20 mm using a bar material with the same material and equivalent hardness as the main sample.
[0058] In step 2-1, each main sample is scanned and analyzed by industrial CT before the experiment to obtain the initial size and position information of the internal defects, the initial diameter of the sample is measured by a vernier caliper, the initial mass of the sample is measured by an electronic balance, the main sample is installed on the driving shaft, and the companion sample is installed on the driven shaft;
[0059] In step 2-2, the theoretical contact stress is set to 1500 MPa, and the corresponding experimental vertical load F = 1565 N is calculated by the formula. At this time, the stress field at a position 2 mm below the contact surface of the main specimen is similar to the stress field at the rim crack 15 mm below the tread of the real wheel. The experimental vertical load is calculated as follows:
[0060] Where a is the semi-major axis of the elliptical contact, F is the vertical load, R is the equivalent radius, and E is the equivalent elastic modulus.
[0061] Where E is the equivalent elastic modulus, v1 and v2 are the Poisson's ratios of the specimen, and E1 and E2 are the elastic moduli of the specimen.
[0062] Where R is the equivalent radius, R1 and R2 are the radii of the specimen respectively.
[0063]
[0064] Where b is the minor semi-axis of the elliptical contact, d1 and d2 are the diameters of the specimen, v1 and v2 are the Poisson's ratios of the specimen, E1 and E2 are the elastic moduli of the specimen, F is the vertical load, and l is the contact line length of the contact area.
[0065] Where P max is the maximum contact stress, b is the minor semi-axis of the elliptical contact, F is the vertical load, and l is the contact line length of the contact area.
[0066] The rotation speed of the main specimen was set to 1000 rpm, and the slip rate was set to 1%. During the experiment, lubricating oil was continuously sprayed onto the rolling contact surface of the specimen. A filter was also set in the circulation system to regularly deal with the waste chips in the testing machine. The rolling contact fatigue testing machine was started to run the oil lubrication experiment at the specified number of cycles.
[0067] In step 3, after running the specified number of cycles, the main sample is removed, ultrasonically cleaned and dried using anhydrous ethanol, the diameter size in the circumferential direction is measured three times using a vernier caliper and the average value is taken, the mass is measured three times using an electronic balance and the average value is taken, the contact surface morphology of the sample is photographed, and the internal crack propagation information of the main sample is recorded using an industrial CT scan, and the specified number of cycles is continued to be run, and the process is repeated until the final set number of cycles is reached;
[0068] In step 4, the industrial CT scan data obtained in step 3 is used to measure the major axis extension size a of the elliptical crack inside the main sample at the specified times. i , minor axis extension dimension b i , crack extension angle θ i , crack area S i , equivalent crack size Draw a relationship curve between the parameter and the number of sample cycles;
[0069] Crack equivalent size The calculation of has the following relationship:
[0070]
[0071] In step 5, statistical analysis is performed on the crack extension size information obtained in step 4, and the secant method is used to calculate the crack extension rate during data processing:
[0072]
[0073] Where C is the crack extension size and N is the number of cyclic loading.
[0074] The relationship curve between crack extension size and crack extension rate is obtained;
[0075] In step 6, after the experiment, if the internal crack of the main sample has expanded to the point of surface shedding, the fracture surface is protected. For the crack area that has not expanded to the point of surface shedding, the electric spark cutting equipment is used to take samples and cut the crack surface. The scanning electron microscope and white light interferometer are used to observe the fracture morphology of the crack extension, and the two-dimensional and three-dimensional information of the crack extension is obtained. The width and height of the fatigue crack are statistically analyzed, and the friction and extrusion conditions and grain refinement phenomenon in the crack area are analyzed. The crack formation mechanism is studied, and a comparative analysis is performed with the actual internal serrated cracks of rolling contact fatigue to verify the effectiveness of the experiment;
[0076] In step 7, by changing the experimental vertical force, rotation speed, slip ratio, lubrication conditions, and number of cycles, the effects of different combined load parameters on crack propagation are analyzed, the initial shape, size, and position of the internal buried defects from the contact surface are changed, and the effects of different initial defects on the crack propagation rate and propagation behavior are analyzed.
[0077] In summary, the rolling contact fatigue internal crack propagation test method based on additive manufacturing proposed in this embodiment is used to solve technical problems such as the difficulty in monitoring the extension process of rolling contact fatigue internal cracks, and the unclear extension path and extension rate. Rolling contact fatigue specimens containing internal buried defects are prepared by additive manufacturing, and rolling contact fatigue experiments are carried out by changing different experimental parameters using a rolling contact fatigue testing machine. The extension behavior of internal cracks under different numbers of cycles is monitored by industrial CT, and the crack extension rate curve is obtained to study the crack formation mechanism. The extension behavior of rolling contact fatigue type II-III composite cracks can be reproduced, providing technical support for the research of engineering problems such as railway wheel rim cracks, rail core damage, bearing raceway surface peeling, and rolling contact fatigue theory.
[0078] Example 2
[0079] In this embodiment, a rolling contact fatigue internal crack propagation test method based on additive manufacturing is provided. Taking wheel rim crack as an example, the formation of rim crack consists of internal crack initiation and zigzag crack propagation. The preset internal defect is relatively large, and it can be considered that the crack has initiated, and only its propagation behavior is studied.
[0080] like Figure 1 As shown in the figure, the main specimen is manufactured by selective laser melting (SLM) additive manufacturing technology of metal materials. In order to increase the probability of internal crack propagation, three buried elliptical defects parallel to the contact surface are preset inside each specimen. The three defects are equidistantly distributed in the circumferential direction of the contact surface with an angle of 120°. The occurrence position of rim cracks is usually 10-25mm below the tread. The internal stress distribution of the rim can be obtained by finite element calculation method, as shown in Figure 3 The stress distribution inside the specimen is also calculated as shown in Figure 4 As shown, in order to simulate the stress state of the real rim crack area, defects are preset in the area inside the main sample that is equivalent to the stress of the real rim crack area. The size and position of the internal defects are set as shown in Table 1. In order to reduce the unmelted powder defects or voids in the additive manufacturing process and eliminate the residual stress, the sample needs to be heat treated;
[0081] Finally, the main sample is processed into a ring sample with a diameter of 60mm, a thickness of 20mm, a rolling boss length of 10mm, a height of 4mm, and a radius of 80mm; the accompanying sample is made of a bar with the same material and equivalent hardness as the main sample and processed into a defect-free ring sample with a diameter of 60mm and a thickness of 20mm, such as Figure 2 As shown;
[0082] Table 1 Size and location of preset internal defects of main specimen
[0083] serial number Defect thickness / mm Defect depth / mm Elliptical defect major axis × minor axis / mm A 0.2 2 3×2 B 0.2 2 4.5×3 C 0.2 2 6×4 D 0.2 1.5 4.5×3 E 0.2 2.5 4.5×3
[0084] Before the formal experiment, each main sample was scanned and analyzed using industrial CT. Figure 3 As shown, the initial three-dimensional size of the internal elliptical defect in the spatial position can be obtained, including the major axis, minor axis, and distance from the contact surface of the ellipse. The molding effect of the internal defect is almost consistent with the design expectation, which verifies the feasibility of SLM technology to preset internal defects. The initial diameter size in the circumferential direction is measured three times with a vernier caliper and the average value is taken. The initial mass is measured three times with an electronic balance and the average value is taken. The main sample is installed on the driven shaft, and the accompanying sample is installed on the active shaft.
[0085] The theoretical contact stress is set to 1500MPa, and the corresponding experimental vertical load F=1565N is calculated by the formula. At this time, the stress field at a position 2mm below the contact surface of the main specimen is similar to the stress field at the rim crack 15mm below the tread of the real wheel. The calculation of the experimental vertical load is as follows:
[0086]
[0087] Where a is the semi-major axis of the elliptical contact, F is the vertical load, R is the equivalent radius, and E is the equivalent elastic modulus.
[0088]
[0089] Where E is the equivalent elastic modulus, v1 and v2 are the Poisson's ratios of the specimen, and E1 and E2 are the elastic moduli of the specimen.
[0090]
[0091] Where R is the equivalent radius, R1 and R2 are the radii of the specimen respectively.
[0092]
[0093] Where b is the minor semi-axis of the elliptical contact, d1 and d2 are the diameters of the specimen, v1 and v2 are the Poisson's ratios of the specimen, E1 and E2 are the elastic moduli of the specimen, F is the vertical load, and l is the contact line length of the contact area.
[0094] Where P max is the maximum contact stress, b is the minor semi-axis of the elliptical contact, F is the vertical load, and l is the contact line length of the contact area.
[0095] The rotation speed of the main sample was set to 1000rpm. In order to simulate the large tangential force caused by wheel-rail slip, the slip rate was set to 1%. In order to reduce the wear on the sample surface, lubricating oil was continuously sprayed onto the rolling contact surface of the sample during the experiment. The lubricating oil was L-HM46 anti-wear hydraulic oil, and the flow rate of the nozzle was set to 1.0L / min. In order to prevent the waste chips in the test machine from affecting the test results, a filter was set in the circulation system to regularly process the waste chips in the test machine. The schematic diagram of the experimental device is shown in the figure. Figure 6 As shown, the specific experimental parameters under the specified number of cycles are shown in Table 2, and the rolling contact fatigue testing machine is started to run the oil lubrication experiment under the specified number of cycles.
[0096] Table 2 Experimental parameters at specified cycle numbers
[0097]
[0098] After running the specified number of cycles, the main sample is removed, ultrasonically cleaned with anhydrous ethanol for 5 minutes and dried with a fan, the diameter size in the circumferential direction is measured three times with a vernier caliper and the average value is taken to calculate the wear depth, the mass is measured three times with an electronic balance and the average value is taken to calculate the wear mass, the contact surface morphology of the sample is photographed, the surface damage is observed and analyzed, the internal crack propagation information of the main sample is recorded by industrial CT scanning, and the specified number of cycles is continued to be run, and the process is repeated until the final set number of cycles is reached;
[0099] Using the industrial CT scanning data obtained each time, measure the major axis extension size a of the elliptical crack inside the main sample at the specified number of times i , minor axis extension dimension b i , crack extension angle θ i , crack area S i , equivalent crack size Draw a relationship curve between the parameter and the number of sample cycles;
[0100] Crack equivalent size The calculation of has the following relationship:
[0101]
[0102] The obtained crack extension size information is statistically analyzed, and the secant method is used to calculate the crack extension rate during data processing. The extension rates of the major axis a and minor axis b of the elliptical crack are calculated respectively:
[0103]
[0104] Where C is the crack extension size and N is the number of cyclic loading.
[0105] The relationship curve between crack extension size and crack extension rate is obtained, and compared with the traditional I-type crack extension characteristics caused by circumferential tension and compression loads, the influence of the upper and lower deflection of RCF zigzag cracks, the friction of the crack surface, and the size of the compressive stress on the internal crack extension of RCF are analyzed, and the extension characteristics of II-III-type cracks inside RCF are obtained;
[0106] After the experiment, if the internal crack of the main sample has expanded to the point of falling off, the fracture surface is protected. For the crack area that has not expanded to the point of falling off, the electric spark cutting equipment is used to sample and cut the crack surface. The scanning electron microscope and white light interferometer are used to observe the crack extension fracture morphology to obtain the two-dimensional and three-dimensional information of the crack extension. Taking the wheel rim crack as an example, the scanning electron microscope image of the rim crack surface is shown in Figure 7 As shown, the white light interference pattern is shown in Figure 8 As shown in the figure, by statistically analyzing the width and height of fatigue cracks, analyzing the friction and extrusion conditions in the crack area and the grain refinement phenomenon, studying the crack formation mechanism, and comparing and analyzing the actual internal serrated cracks in rolling contact fatigue, the validity of the experiment is verified.
[0107] By changing the experimental vertical force, rotation speed, slip ratio, lubrication conditions, and number of cycles, the effects of different combined load parameters on crack growth are analyzed. The initial shape, size, and position of the internal buried defects from the contact surface are changed to analyze the effects of different initial defects on the crack growth rate and growth behavior.
[0108] Table 3 Experimental parameters under different initial defect sizes
[0109]
[0110] Table 4 Experimental parameters at different initial defect depths
[0111]
[0112]
[0113] In summary, in order to solve the technical problems such as the difficulty in monitoring the extension process of internal cracks in rolling contact fatigue, unclear extension path and extension rate, rolling contact fatigue specimens with internal buried defects were prepared by additive manufacturing. The RCF test was carried out by changing different load parameters using a rolling contact fatigue testing machine. The extension of internal cracks was observed by industrial CT, and the extension behavior of rolling contact fatigue type II-III composite cracks was truly simulated. The formation mechanism of the cracks was studied, which provided technical support for the research on engineering problems such as railway wheel rim cracks, rail core damage, bearing raceway surface peeling, and rolling contact fatigue theory.
[0114] Although the above describes the specific implementation mode of the present invention in conjunction with the accompanying drawings, it is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that various modifications or variations that can be made by those skilled in the art without creative work on the basis of the technical solution disclosed in the present invention should be included in the scope of protection of the present invention.
Claims
1. A rolling contact fatigue internal crack growth test method based on additive manufacturing, characterized in that: The method comprises the following steps: Prepare rolling contact fatigue main specimens with internal buried defects and defect-free companion specimens; Conduct rolling contact fatigue test: pre-treat the specimen to determine the initial defects of internal defects; determine the experimental parameters, start the rolling contact fatigue test machine to run the oil lubrication test under the specified number of cycles; The main sample is removed, the contact surface morphology of the sample is photographed, the mass and diameter of the sample are measured, the internal crack extension is photographed using industrial CT, and the process is repeated after the specified number of cycles. Obtain the relationship between the major axis and minor axis extension size, extension angle, crack area, equivalent crack size and the number of sample cycles of the elliptical crack inside the main sample under the specified number of times; Calculate the growth rate of internal buried cracks; After the experiment, the crack area that has not extended to the surface was sampled using an electric spark cutting device and the crack surface was cut open. The crack extension fracture morphology was observed using a scanning electron microscope and a white light interferometer to obtain the crack size information. Analyze the growth rate and growth behavior of different combined load parameters and different initial cracks.
2. The rolling contact fatigue internal crack growth test method based on additive manufacturing according to claim 1, characterized in that: The main specimen was manufactured using additive manufacturing technology, and a buried elliptical defect was preset inside each specimen. Finally, the main specimen was processed into an annular specimen with a diameter of 60 mm, a thickness of 20 mm, a rolling boss length of 10 mm, a height of 4 mm, and a radius of 80 mm; the companion specimen was made of a rod with the same material and equivalent hardness as the main specimen and processed into an annular specimen with a diameter of 60 mm and a thickness of 20 mm.
3. The rolling contact fatigue internal crack growth test method based on additive manufacturing according to claim 1, characterized in that: Before the experiment, industrial CT was used to scan and analyze each main sample to obtain the initial size and position information of internal defects. The initial diameter of the sample was measured with a vernier caliper, and the initial mass of the sample was measured with an electronic balance. The main sample was installed on the driving shaft, and the companion sample was installed on the driven shaft.
4. The rolling contact fatigue internal crack growth test method based on additive manufacturing according to claim 1, characterized in that: The theoretical contact stress is set to 1500MPa, and the corresponding experimental vertical load F=1565N is calculated by the formula. At this time, the stress field at a position 2mm below the contact surface of the main specimen is similar to the stress field at the rim crack 15mm below the tread of the real wheel.
5. The rolling contact fatigue internal crack growth test method based on additive manufacturing according to claim 4, characterized in that: The rotation speed of the main specimen was set to 1000 rpm, and the slip rate was set to 1%. During the experiment, lubricating oil was continuously sprayed onto the rolling contact surface of the specimen. A filter was also set in the circulation system to regularly deal with the waste chips in the testing machine. The rolling contact fatigue testing machine was started to run the oil lubrication experiment at the specified number of cycles.
6. The rolling contact fatigue internal crack growth test method based on additive manufacturing according to claim 1, characterized in that: After running the specified number of cycles, the main sample is removed, ultrasonically cleaned and dried with anhydrous ethanol, the diameter in the circumferential direction is measured three times with a vernier caliper and the average value is taken, the mass is measured three times with an electronic balance and the average value is taken, the contact surface morphology of the sample is photographed, and the internal crack propagation information of the main sample is recorded using an industrial CT scan. The specified number of cycles is continued to be run, and the process is repeated until the final set number of cycles is reached.
7. The rolling contact fatigue internal crack growth test method based on additive manufacturing according to claim 1, characterized in that: Using the industrial CT scanning data obtained, the major axis extension size a of the elliptical crack inside the main sample at a specified number of times is measured. i , minor axis extension dimension b i , crack extension angle θ i , crack area S i , equivalent crack size Draw a curve diagram of the relationship between the parameters and the number of sample cycles.
8. The rolling contact fatigue internal crack growth test method based on additive manufacturing according to claim 1, characterized in that: The obtained crack extension size information is statistically analyzed, and the secant method is used to calculate the crack extension rate during data processing: Where C is the crack extension size, N is the number of cyclic loading; The relationship curve between crack extension size and crack extension rate is obtained.
9. The rolling contact fatigue internal crack growth test method based on additive manufacturing according to claim 1, characterized in that: After the experiment, if the internal crack of the main sample has extended to the surface and fallen off, the fracture surface will be protected. For the crack area that has not extended to the surface and fallen off, the electric spark cutting equipment is used to take samples and cut the crack surface. The scanning electron microscope and white light interferometer are used to observe the crack extension fracture morphology, and the two-dimensional and three-dimensional information of crack extension is obtained. The width and height of the fatigue crack are statistically analyzed, and the friction and extrusion conditions and grain refinement phenomena in the crack area are analyzed. The crack formation mechanism is studied, and a comparative analysis is performed with the actual internal serrated cracks of rolling contact fatigue to verify the effectiveness of the experiment.
10. The rolling contact fatigue internal crack growth test method based on additive manufacturing according to claim 1, characterized in that: By changing the experimental vertical force, rotation speed, slip ratio, lubrication conditions, and number of cycles, the effects of different combined load parameters on crack propagation are analyzed. The initial shape, size, and position of the internal buried defects from the contact surface are changed, and the influence of different initial defects on the crack propagation rate and propagation behavior are analyzed.
Citation Information
Patent Citations
Accelerated rolling contact fatigue test method of metal material in small slip ratio
CN103424307A
Method for detecting and analyzing internal defect evolution of metal casting in fatigue process
CN104515786A
Fatigue crack three-dimensional expansion comparative analysis method for off-line CT detection condition
CN104865139A
3D printing technology based artificial initial cracks containing rock-like specimen preparation method
CN108240930A
Preparation method for prefabricating crack defect, preparation method of built-in crack defect and prefabricated member with built-in crack defect
CN111203538A
Cited By
INSTALLATION FOR PRODUCING CRACKS IN RING SPECIMENS FROM STEEL
RU236345U1